PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA PERUMBULOG KANWIL SUMUT - EVI RESEPINA Br. SEMBIRING (JOURNAL ECONOMICS AND STRATEGY, 2021)
The writer used a quantitative descriptive method to research—population in this study, an employee of the North Sumatra Region BULOG Perum Office. The research sample was 43 people. The data collection technology used to distribute questionnaires/questionnaires using a Likert scale model. the estimated effect of the variables, multiple linear regression analysis was used with a confidence level of 95 percent (alpha = 0.05%). Data processing is indicated by the t value of leadership style and organizational culture, namely 2.492 and 2.156. These values ​​are above the t table value of 1.681, and the significant importance ​​of each variable is 0.017 and 0.007. This result explains that the leadership style (x1) and organizational culture (x2) individually have a significant and positive effect on employee performance (Y). The results of the F test are indicated by the F count, which is> from the F table number (6.047> 2.824), and the significant value is <0.05 (0.005 <0.05). Suggests that leadership style (x1) and organizational culture (x2) together have a positive and significant effect on employee performance (Y). Meanwhile, R square's value was obtained 0.723 (72.30%), which means that employee performance can be explained up to 72.30% by organizational culture and leadership style.